Economy-wide impacts of reduced wait times at U.S. international airports. (September 2015) - Prager, Fynnwin; Rose, Adam; Wei, Dan; Roberts, Bryan; Baschnagel, Charles
Abstract: Passport and customs inspections monitor the cross-border flows of people and goods, and are a "bottleneck" in the international transportation system that can cause significant and costly wait times for many passengers. U.S. passport inspection wait times have been criticized in recent years, and recent studies show that small changes in U.S. inspection wait times could change international travel demand, impact U.S. economic sectors reliant on international travel, and generate further impacts across the economy. This paper estimates economy-wide impacts of reduced passport inspection wait times at four international airports under two scenarios: 1) adding one Customs and Border Protection (CBP) officer to each of the 14 inspection sites and 2) reducing inspection wait times by 50%. We simulate the economy-wide GDP and employment impacts of these international travel-related spending changes using a computable general equilibrium model of the U.S. economy that accounts for price and substitution effects across supply-chain linkages. Adding 14 officers in the four airports is estimated to increase GDP by $4.5 to $11.7 million and add 36 to 93 jobs across the economy. A 50% wait time reduction at these four airports is estimated to increase GDP by $81.5 m to $260.7 m, and add 651 to 2152 jobs to the U.S. economy.